Priming and pretreatment of seeds and seedlings : implication in plant stress tolerance and enhancing productivity in crop plants - (:unkn) unknown (My University, 2019)
This book introduces readers to both seed treatment and seedling pretreatments, taking into account various factors such as plant age, growing conditions and climate. Reflecting recent advances in seed priming and pretreatment techniques, it demonstrates how these approaches can be used to improve stress tolerance and enhance crop productivity. Covering the basic phenomena involved, mechanisms and recent innovations, the book offers a comprehensive guide for students, researchers and scientists alike, particularly Plant Physiologists, Agronomists, Environmental Scientists, Biotechnologists, and Botanists, who will find essential information on physiology and stress tolerance. The book also provides a valuable source of information for professionals at seed companies, seed technologists, food scientists, policymakers, and agricultural development officers around the world.
Keywords: Cross tolerance; Abiotic stress; Seed biology; Priming and seedlings; Seed treatment